The Erbium laser in the debonding of ceramics: a literature review - Zanini, Nathalia Alves; Caramel-Juvino, Amanda; Ana, Patrícia Aparecida; Zezell, Denise (Brazilian Dental Science, 2022)
Background: The debonding of crowns and ceramic veneers with laser is already a reality in the clinic. It presentsbenefits in comparison to traditional removal with the use of a rotating instrument; however, there is still noconsolidated protocol and many professionals use it without the necessary scientific basis. Objective: The aim ofthis work was to perform a literature review on the debonding of indirect ceramic restorations using the Er:YAGand Er,Cr:YSGG lasers to provide clinical professionals and the scientific community a careful analysis, and alsoto guiding the use of irradiation at laser for such procedures. Methods: Bibliographic searches were performed inthe following databases: Pubmed, Web of Science and Google Scholar. According to the inclusion criteria adopted,twenty-seven clinical and in vitro studies were selected in the period from 2007 to 2021. In the present work, thecomposition of the crowns and facets, as well as the types of cement and the laser irradiation protocols adoptedin the selected studies is detailed. Conclusions: It was concluded that the use of erbium lasers for debondingof indirect ceramic restorations proved to be more selective and conservative when compared to removal witha rotary diamond instrument. Furthermore, it was shown to be in more efficient in debonding different typesof ceramics. However, there are great variations in the “debonding” protocols, which emphasizes the need forfurther studies that seek to standardize the irradiation protocols considering the different clinical situations.KEYWORDSVeneers debonding; Debonding; Er,Cr:YSGG laser; Er:YAG laser; Ceramics.